Durability Analysis of a Magneto-Rheological Fluid for Automotive Braking System - Giovanni Imberti; Henrique de Carvalho Pinheiro; Matteo De Carlo; Guglielmo Peruzzi; Massimiliana Carello (Designs)
The automotive market is looking for innovative braking solutions that can mitigate or eliminate secondary emissions. For this reason, new braking paradigms have been developed, and magnetorheological brakes could be considered a suitable solution due to their performance and controllability features. Reliability is a key factor for automotive braking systems, so it is essential to analyze the behavior of such technological solutions in iterative cycles to understand their capability of maintaining brake performance throughout their operative lifecycles. This article presents a preliminary experimental durability analysis and defines the testing standard procedures to be used as boundaries for this analysis. Then, a durability test bench is developed and produced to evaluate the magnetorheological fluid over an equivalent distance of 100,000 km. After the tests, the fluid’s characteristics are compared to its original features using a rheometer apparatus and Scanning Electron Microscopy (SEM).